Weight Loss and Calorie Restriction at 50% Fasting Rate - Jennings, John H.; Lesser, Michael (Pakistan Journal of Nutrition, 2012)
In planning a diet with the purpose of weight loss, a doctor will invariably need to cut back calories consumed by the patient. As a rule of thumb, 3500 cal/lb is the calories eliminated for loss of one pound of body weight. This work is a pilot study to see the relation between the calorie deficit and the rate of weight loss in humans. A random search was made for data points and the search was stopped when the average fasting rate was about 50% and N = 51 data points were found. Water loss enters in and people have different metabolisms, so the 3500 figure has an uncertainty of about 20%. The author performed the literature search, in addition to adding his own data and he came up with a new value of 3511 cal/lb. This result originates from calorie restriction data on an otherwise normal diet in terms of the proportion of fat, carbohydrate and protein. The well-known result of 3500 cal/lb agrees with data from diets at a 50% fasting rate. Evidently the 3500 cal/lb figure holds throughout the entire fasting range.